2020
DOI: 10.3390/ijms21217922
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Induced by Chronic Liver Disease in Mice Requires the Expression of the Bile Acids Membrane Receptor TGR5

Abstract: Sarcopenia is a condition of muscle dysfunction, commonly associated with chronic liver disease (CLD), characterized by a decline in muscle strength, the activation of the ubiquitin-proteasome system (UPS), and oxidative stress. We recently described a murine model of CLD-induced sarcopenia by intake of hepatotoxin 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC), which presents an increase in plasma bile acids (BA). BA induced skeletal muscle atrophy through a mechanism dependent on the Takeda G protein-couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Together, these results suggest that high serum concentrations of BA induce hepatic oxidative stress. 5 Oxidative Medicine and Cellular Longevity Our laboratory described the induction of sarcopenia in a mice model of cholestatic liver disease characterized by TGR5-dependent mechanisms: (1) oxidative stress, presenting elevated ROS, carbonylated proteins, and 4-HNE in skeletal muscles; (2) increased myonuclear apoptosis, with induction of the caspase pathway and increased Bax/Bcl-2 ratio; and (3) induction of protein catabolism through UPS [54,107,109]. Interestingly, ROS is directly associated with the UPS induction and mitochondrial alterations that might induce apoptosis [108,[110][111][112].…”
Section: Redox-dependent Mechanisms Participate In Damage Induced By Bile Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these results suggest that high serum concentrations of BA induce hepatic oxidative stress. 5 Oxidative Medicine and Cellular Longevity Our laboratory described the induction of sarcopenia in a mice model of cholestatic liver disease characterized by TGR5-dependent mechanisms: (1) oxidative stress, presenting elevated ROS, carbonylated proteins, and 4-HNE in skeletal muscles; (2) increased myonuclear apoptosis, with induction of the caspase pathway and increased Bax/Bcl-2 ratio; and (3) induction of protein catabolism through UPS [54,107,109]. Interestingly, ROS is directly associated with the UPS induction and mitochondrial alterations that might induce apoptosis [108,[110][111][112].…”
Section: Redox-dependent Mechanisms Participate In Damage Induced By Bile Acidsmentioning
confidence: 99%
“…Recently, our group demonstrated that DCA and CA, in a TGR5-dependent manner, induced sarcopenia and atrophy in skeletal muscle by incrementing the ubiquitin-proteasome system (UPS) and oxidative stress [ 44 ]. Also, the absence of the TGR5 receptor prevents the sarcopenia induced by cholestatic chronic liver disease, protecting the muscle from loss of mass and strength [ 54 ]. These results contradict a report indicating that TGR5 enhances muscle differentiation in the C2C12 myoblast and induces hypertrophy in mice [ 45 ].…”
Section: Bile Acid Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, GMM that can modulate inflammation signaling pathways, such as SCFAs, can affect normal skeletal muscle metabolism and cause muscle wasting. Indeed, various studies have been demonstrated that SCFAs play a profound role in regulating muscle mass and physical function [131] . There are studies that suggest that liver disease, which causes abnormal production of BAs, may lead to muscle wasting and cachexia [132,133] .…”
Section: The Gut-muscle Axis: Interplay Between Gut Microbial Metabol...mentioning
confidence: 99%
“…Indeed, various studies have been demonstrated that SCFAs play a profound role in regulating muscle mass and physical function [ 131 ] . There are studies that suggest that liver disease, which causes abnormal production of BAs, may lead to muscle wasting and cachexia [ 132 , 133 ] . However, currently, there is no study evaluating the GMM-BAs associated with sarcopenia.…”
Section: Contributions Of the Gut Microbiome In Heart Failure And Sar...mentioning
confidence: 99%